A phase 1b study of OXIRI in pancreatic adenocarcinoma patients and its immunomodulatory effects. Issue 3 (6th May 2022) - Ng, Matthew; Chen, Sylvia; Ong, Whee Sze; Balachander, Akhila; Seet, Amanda; Yeong, Joe; Sutiman, Natalia; Lim, Tony Kiat Hon; Lee, Bernett; Guo, Yu Amanda; Leong, Wai Fook; Lee, Sze Sing; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal and debilitating disease with limited therapeutic options. The aim of this clinical study was to evaluate the safety, efficacy and pharmacokinetics of a novel regimen comprised of metronomic oxaliplatin (O), chronomodulated capecitabine (X) and UGT1A1 genotype‐guided dosing of irinotecan (IRI) [OXIRI] as well as its immunomodulatory effects. Thirty‐six patients were enrolled into either dose‐escalation or expansion cohorts. In the dose escalation phase, capecitabine doses (2000, 2650, 3500 and 4500 mg/day) were administered at midnight on days 1 to 14 while oxaliplatin and irinotecan were intravenously infused at fixed doses of 50 and 75 mg/m 2 respectively on days 1, 8 in a 21‐day cycle. The maximum tolerated dose of capecitabine was 2650 mg/day and the most common grade 3 adverse events were neutropenia (30.6%) and diarrhea (13.9%). No grade 4 toxicity was observed. UGT1A1 ‐genotype directed dosing resulted in similar exposure levels of irinotecan, SN‐38 and SN‐38G in all patients. Objective response rate was 22.2%. Median overall survival and progression‐free survival were 8.1 and 5.2 months, respectively. Exploratory immunoprofiling by flow cytometry and quantitative spatial localization analysis of infiltrated immune cells performed on biopsy and plasma samples revealed significant declines in CCL22, CCL2 and TNFα levels at end of first cycle and an active host immune response. Our study showed that OXIRI was well‐tolerated and exhibited good efficacy, with immunomodulatory effects. It may be considered as an alternative to FOLFIRINOX in patients intolerant to the latter. Abstract : What's new? Intolerability due to serious toxicity is often the cause of treatment failure in metastatic pancreatic ductal adenocarcinoma. Our study reports on the clinical results from a phase 1b study of a novel regimen formed of metronomic oxaliplatin (O), chronomodulated capecitabine (X) and UGT1A1 genotype‐guided dosing of irinotecan (IRI) [OXIRI] in heavily pretreated locally‐advanced/metastatic pancreatic ductal adenocarcinoma patients. The results show that OXIRI is well‐tolerated with a good safety profile and has promising efficacy. The multiparametric immunoprofiling of patients also suggests that OXIRI may exert an immunomodulatory effect on pancreatic ductal adenocarcinoma.